تقييم الأداء المالي لبنك سورية الدولي الإسلامي دراسة تطبيقية خلال الفترة 2008-2012 - نادر, نهاد; الأمير سليمان, مايا مالك (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يتناول البحث تقييم الأداء المالي لبنك سورية الدولي الإسلامي خلال الفترة 2008-2012 من خلال عرض وتحليل وتفسير أهم مكونات القوائم المالية في البنك والتي تشمل: تحليل الأصول (استخدامات الأموال). تحليل الخصوم (مصادر الأموال). تحليل الموارد الذاتية, وهي: (تحليل رأس المال الأسهم المدفوع, تحليل الاحتياطات, تحليل الأرباح المدورة, تحليل حقوق الملكية). تحليل الموارد الخارجية (الودائع). تحليل الاستثمارات. تحليل الإيرادات. تحليل الربحية. تحليل الملاءة المالية. وباستخدام الأساليب الإحصائية المناسبة كمعدل التغير السنوي, ومتوسط معدل النمو, والانحدار البسيط, تمّ التوصل إلى النتائج الآتية: 1- تنمو الأصول (استخدامات الأموال) بمعدلات متزايدة, وهذا يدل على قدرة بنك سورية الدولي الإسلامي على توليد تدفقات نقدية مستقبلية, بما يجعله يتمتع بكفاءة عالية في أدائه المالي. 2- تنمو الخصوم (مصادر الأموال) متزايدة بشكل مستمر, وهذا يدل على أن البنك يقوم بعملية جذب الودائع وتنميتها, نتيجة الثقة التي اكتسبها من قبل المودعين مما ينعكس ايجاباً على أدائه المالي. 3- حققت الإيرادات معدلات نمو مرتفعة في معظم سنوات الدراسة, وكانت المرابحة والاستصناع, والإجازة المنتهية بالتمليك هي الصيغ المستخدمة ضمن ايرادات الأنشطة التمويلية. 4- تنمو الاستثمارات بمعدلات منخفضة مع الزمن في معظم سنوات الدراسة, حيث أن هناك صيغ إسلامية استثمارية كالمزارعة والمساقاة.. وغيرها لم يدخل فيها المصرف بعد, كما أن هناك بعض الصيغ دخل فيها المصرف بشكل محدود كالمضاربة والمشاركة. This research deals with evaluating the financial performance of Syria International Islamic Bank during the period 2008-2012 through the presentation, analysis and interpretation of the most important components of the financial statements of the bank, which include: analysis of assets (uses of funds). Analysis of liabilities (sources of funds). Analysis of own resources, namely: (analysis of capital stock paid, analyzing reserves, retained earnings analysis, analysis of property rights). Analysis of external resources (deposits). Investment analysis. Analysis of revenue. Profitability Analysis. Analysis of financial solvency. Using statistical methods appropriate average annual change, and the average growth rate, and simple regression, was reached following results: 1 - grow assets (uses of funds) at an increasing rate, and this demonstrates the ability of Syria International Islamic Bank to generate future cash flows, including it with high efficiency in its financial performance. 2 - grow liabilities ( sources of funds) increased continuously, and this indicates that the bank is the process of attracting deposits and development, as a result of the confidence gained by depositors which will reflect positively on its financial performance. 3- Revenue achieved high growth rates in most of the years of study and was Murabaha istisna, and leave ended Bittamleek formulas are used within the revenue from financing activities. 4 - low rates of investment grow with time in most years of the study, where there is an Islamic investment Kalmzarah formats and Musaqah. and the other did not enter the bank yet, as there are some formulas entered the bank in a limited way Kalmdharbh and participation.